2019
DOI: 10.1002/aic.16856
|View full text |Cite
|
Sign up to set email alerts
|

High expression of toxic Streptomyces phospholipase D in Escherichia coli under salt stress and its mechanism

Abstract: Phospholipase D (PLD) cytotoxicity limits its high heterologous expression and further application in the food industry. The specific physiological consequences of highly expressed PLD in vivo are unclear. In this study, we observed that PLD expression by Escherichia coli caused phosphatidic acid accumulation and membrane permeability enhancement, characterized by the disruption of ionic homeostasis with enhanced K+ efflux and Na+ influx, which eventually may result in cell injury or death. Moreover, we found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…(S7 Table). In recent study, Xiong and co-workers [63] reported the genes responsible for membrane transport, abc transport, glycine betaine and proline in E. coli under salt stress which corroborates to our present study. A similar study has De novo transcriptome analysis of halotolerant bacterium Staphylococcus sp.…”
Section: Discussionsupporting
confidence: 93%
“…(S7 Table). In recent study, Xiong and co-workers [63] reported the genes responsible for membrane transport, abc transport, glycine betaine and proline in E. coli under salt stress which corroborates to our present study. A similar study has De novo transcriptome analysis of halotolerant bacterium Staphylococcus sp.…”
Section: Discussionsupporting
confidence: 93%
“…Xiong et al found that the PLD-imposed cells in E. coli underwent ion perturbations, resulting in cell injury or cell death. Na + stress protects the PLD-imposed cells by improving oxidative phosphorylation through a positive change in the membrane potential via redistribution of Na + /K + inside and outside the cell [ 25 ]. Therefore, B. choshinensis/ pNCMO2 was cultured in medium A without Mg 2+ (NP group), and B. choshinensis /pNCMO2-PLD was cultured in medium A (EPMg group) and without Mg 2+ (EP group) to determine whether Mg 2+ has a similar regulatory mechanism for PLD expression.…”
Section: Resultsmentioning
confidence: 99%
“…subtilis [ 24 ], but their extracellular synthesis with high-efficiency is still strenuous due to their cytotoxicity [ 20 , 21 ]. According to reports, the highest PLD production in E. coli Top10 was 1100 U/mL [ 25 ], but it was intracellular expression. The extracellular expression systems have recently gained increased attention due to the easy separation and production of extracellular PLD.…”
Section: Introductionmentioning
confidence: 99%
“…However, after 24 h, [K + ] began to decrease accompanied by an increase in [Na + ] content in the EP group, while in the EPMg group, [K + ] continued to increase accompanied by a steady low [Na + ]. In 24 h, the continued PLD expression in the cell caused K + e ux and Na + in ux in the EP group, which was harmful to the cells [25]. However, the addition of Mg 2+ could regulate the change in ions.…”
Section: Ion Perturbation In the Pld-imposed Cellsmentioning
confidence: 95%
“…subtilis [24], but their extracellular synthesis with high-e ciency is still strenuous due to their cytotoxicity [20,21]. According to reports, the highest PLD production in E. coli Top10 was 1100 U/mL [25], but it was intracellular expression. The extracellular expression systems have recently gained increased attention due to the easy separation and production of extracellular PLD.…”
Section: Introductionmentioning
confidence: 99%